PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI PADA MATA PELAJARAN IPS UNTUK SISWA KELAS III SD/MI - Suciana Fatia; Sri Nurhayati; Septio Putra; Suci Ramadhani; Ridwan; Susi Ratna Sari (STKIP Subang, 2026)
This study aims to create animated video-based teaching media for Social Studies (IPS) lessons for 3rd grade elementary school students, focusing on the Natural and Artificial Environment and Types of Jobs. The background of this study is the lack of interesting learning media variations that are appropriate to the characteristics of early childhood who tend to be more interested in moving visual displays and sound. The method used is Research and Development (R&D) with the ADDIE model consisting of five phases: Analysis, Design, Development, Implementation, and Evaluation. This study applies a mixed method approach, where a qualitative approach is used to explore needs, describe the development process, and interpret data from expert validation results. The quantitative approach is used to measure the level of feasibility, practicality, and effectiveness of the media. Product validation was carried out by two material experts and two media experts who assessed aspects of content, presentation, language, and design and technical aspects of the media. Product trials were conducted on 30 3rd grade elementary school students using questionnaires and learning outcome tests as instruments. The results of the study showed that the developed animated video media obtained a validation score from material experts of 87.5% and from media experts of 91.2%, both of which are included in the very feasible category. Student responses to the media reached 88.6% with a very good category. In addition, there was an increase in student learning outcomes as indicated by the N-Gain value of 0.67 in the moderate category. Based on these findings, it can be concluded that the developed animated video-based learning media has proven to be feasible, practical, and effective for use in learning social studies for grade 3 elementary school/Islamic elementary school. This study recommends that teachers use similar media to create a more interactive and enjoyable learning atmosphere.